Sequential determination of titratable acidity and tartaric acid in wines by flow injection spectrophotometry - Rangel, António O. S. S. (2011)
A flow injection manifold is proposed for the sequential determination of titratable (total) acidity based on a pseudotitration and of tartaric acid based on the formation of a coloured vanadate complex. The method involves in-line dialysis prior to injection to avoid interference from the sample background absorption in the spectrophotometric detection. The changes in the colour of both reactions were monitored using two flow cells aligned in the optical path of a single spectrophotometer. Wine samples were analysed without any sample pre-treatment; table wines in the range 1–10 g l21 (total acidity) and 0.5–4 g l21 (tartaric acid) and port wines in the range 1–8 g l21 (total acidity) and 0.5–5 g l21 (tartaric acid). Sixteen samples can be measured per hour, and the results were comparable to those obtained by reference procedures for both determinations. RSDs (n = 10) generally lower than 3% were obtained